Factors Associated With Field Level Extension Workers' Perception of Their Role Performance in the Training and Visit System in Nepal - Kafle, Banik Raj (1993)
Effective role performance of field level extension workers is an important issue for the efficient implementation of agricultural extension systems. In Nepal, more than half of the cultivated land is not covered by proper extension services (MOA, 1989). The training and visit (T&V) system of agricultural extension was introduced with the objective of reforming the agricultural extension services particularly in the terai region of the country. Therefore, the perception of role performance of field level extension workers under the T&V system is a relevant problem for study. The general objective of this study was to determine the factors relating to the perception of role performance of field level extension workers. This study was conducted in three terai districts of Dhanusha, sarlahi and Nawalparasi which were under the T&V extension system. These districts were randomly selected from eight districts under the first phase of Agricultural Extension and Research Project of the T&V system. The respondents for the study were 105 field level extension workers of the districts selected for the study. The findings of the study reveal that though two-thirds of the respondents perceived that they performed their assigned roles satisfactorily, higher level of performance was possible. The perception of role performance of field level extension workers was found to be significantly related to work experience, maritalstatus, residential facility, attitude towards subordinates, attitude towards supervisors, attitude towards farmers, attitude towards motivational factors, role perception, and perception towards motivational factors. Among the four groups of variables, altogether role perception contributed 27 percent of the variability in role performance while 19 and 18 percent role performance could be attributed to attitudinal and motivational factors respectively. Personal factors itself contributed ten percent of the variability in the role performance of field level extension workers. Promotional avenues, salary and the provision of allowances were also found to be important determining factors in perception of role performance.